Returning our education to learning - Abd Razak, Dzulkifli (2009)
EMPLOYABILITY, employability, employability. This has been the chant that is repeated annually when it comes to determining how successful the education system is. It is largely led by the marketplace which over time has come to be the driver of education while the educationists slowly recede into the background and abdicate their academic leadership. Backed by shortsighted politicians, the marketplace is emboldened to demand even more tailoredmade courses that must grease the industrial cogs and wheels. The ultimatum—either be "marketable" or be condemned as "irrelevant". Overnight, the purposes of education are fixated on "earning" rather than "learning".